BOOK REVIEW: Arun Mahapatra, art of retailing. New Delhi: Lotus press publishers & distributors, 2015, 156 pp. ISBN: ‎ 978-81-8382-208-4 - Isaac Kazungu; Emmanuel Chao (African Business Management Journal)
With a rising scholarly and practical interest in retailing, the global retail industry is experiencing significant growth. This trend is anticipated to persist, capturing widespread attention from various economic sectors, consumers, entrepreneurs, and investors in the coming decades. The industry is poised for expansive global magnification, fostering job creation and socio-economic development. This review aims to elucidate the integration of the retailing industry within the logistics of business growth. "Art of retailing" emerges as a valuable resource for retail industry professionals, lecturers, professors, and university students engaged in business studies, marketing, procurement, and entrepreneurship programs. Despite its merits, the text's principal drawback lies in its failure to present world-class illustrations, case studies, exhibits, checkpoint questions, and summaries, which are pivotal for reinforcing concepts in each chapter. Nevertheless, researchers in the retail sector can benefit from the contextual insights and identified gaps, paving the way for further studies. The untapped areas highlighted in the text are recommended to enhance the book's significance in the context of the pivotal subject of e-retailing in the contemporary era.